THE EFFECT OF ORGANIC FERTILIZER AND COMBINATION OF NPK ON GROWTH AND YIELD OF PEANUT ON ULTISOL SOIL - Azhar Ansi (Jurusan Penyuluhan Pertanian FP UHO, 2025)
The aim of the research was to study the effect of organic fertilizer and combination of NPK on the growth and yield of peanus on ultisol soils. The study was conducted in the Labibia sub district, Kendari city, from JanuaryMarch to July 2024. The study was arranged in a randomized block design (RBD) in a factorial pattern with three replications consisting of 2 factors. The first factor was organic fertilizer which consisted of 4 levels, namely: control (B0), 5 t ha-1 (B1), 10 t ha-1 (B2), and 15 t ha-1 (B3). The second factor was combination of NPK fertilizer which consisted of 3 levels, namely control (P0), 50 kg ha-1 (P1), and 100 kg ha-1 (P2) so that there were 4x3x3=36 experimental units. Observation variables included: plant height, leaf area, weight of 100 seeds, yield per plot and yield per ha. The results showed that there was an interaction between organic fertilizer and combination of NPK fertilizer on the observed variables. The best results were obtained in the treatment of 15 t ha-1 of organic fertilizer and 100 kg combination1 of NPK fertilizer with the highest production reaching 1,300 t ha-1.